THE DETERMINATION OF THE BIVALVAE Mactra sp. POPULATION COHORT AT REMBANG WATERS, CENTRAL JAVA USING THE BHATTACHARYA METHOD - Muhammad Zainuri (JOURNAL OF COASTAL DEVELOPMENT, 1998)
The determination of bivalvae Mactra sp. Year class cohort were applied for the samples from Randu Guntinh Esturian, Rembang Waters, Central Java, using the Bhattacharya Method (different logarithmatic). The abundance and shell length data of bivalvae Mactra sp collected on March to June, 1996 were used to improved the method. The Bhattacharya method allowed the determination of three year class cohorts for the samples. This discussed in regard to advantage of the method giving the input data for the construction of the growth model.